KONSERVASI HUTAN DAN LAHAN MELALUI PEMBERDAYAAN MASYARAKAT SEKITAR HUTAN - Mawardi, Ikhwanuddin (Jurnal Teknologi Lingkungan, 2006)
Forest resources are really under pressure nowadays and leave only theconservation areas, although they are already standing on a risky zone ofencroachments and illicit felling. The most important issues to beaddressed in order to enable social forestry and work toward alleviatingpoverty security of land and resource tenure and access, and useplanning, streamlined mechanisms for registering rights and resolvingconflicts.